1998
DOI: 10.1152/ajpgi.1998.274.1.g80
|View full text |Cite
|
Sign up to set email alerts
|

Erythromycin gastrokinetic activity is partially vagally mediated

Abstract: Erythromycin overcomes postvagotomy gastroparesia in patients without a distal stomach and functional pylorus. We investigate the role of the vagus in gastric emptying increased by erythromycin, using a model that preserves the physiology of the distal stomach and pylorus. The effects of erythromycin lactobionate (10 mg/kg) on transpyloric flow pattern and pyloric resistance were evaluated during repetitive bilateral vagal cooling in anesthetized pigs. Vagal cooling during erythromycin infusion produced a mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…The authors also found that in addition to facilitation of gastric cholinergic activity, low concentrations of motilin directly increased the activity of a population of gastric vagal afferent fibres. These data substantiate previous indirect evidence suggesting that motilin receptor agonists could influence vagal nerve activity (e.g., Mathis and Malbert (1998);Suzuki et al (1998)) and raise the possibility that erythromycin reduced emesis by stimulating gastric emptying and/or modulating an emetic pathway via changes in vagal afferent nerve activity. A further action of erythromycin within the brain remains a possibility but at present, there is no clear evidence for a direct ability of motilin to affect brain functions .…”
Section: Can Gastric Prokinetic Drugs Relieve Nausea?supporting
confidence: 89%
“…The authors also found that in addition to facilitation of gastric cholinergic activity, low concentrations of motilin directly increased the activity of a population of gastric vagal afferent fibres. These data substantiate previous indirect evidence suggesting that motilin receptor agonists could influence vagal nerve activity (e.g., Mathis and Malbert (1998);Suzuki et al (1998)) and raise the possibility that erythromycin reduced emesis by stimulating gastric emptying and/or modulating an emetic pathway via changes in vagal afferent nerve activity. A further action of erythromycin within the brain remains a possibility but at present, there is no clear evidence for a direct ability of motilin to affect brain functions .…”
Section: Can Gastric Prokinetic Drugs Relieve Nausea?supporting
confidence: 89%
“…129 -131 While erythromycin acts via motilin receptors, an intact vagal pathway has been shown to be necessary for its GI effects. 132,133 Metoclopramide is another prokinetic agent that is useful in the treatment of gastroduodenal hypomotility. 134,135 The precise mechanism of action is unclear, but metoclopramide improves antroduodenal coordination and reverses the inhibitory effects of dopamine on GI motility.…”
Section: Srmdmentioning
confidence: 99%
“…Vagal nerves are considered to play an important role in the regulation of stomach functions [50][51][52][53][54]. In the porcine stomach, vagal afferents constitute up to 80% of afferent pyloric innervation, while only a minority of cell bodies are dispersed within the bilateral spinal ganglia of the thoracic and lumbar neuromeres [7].…”
Section: Discussionmentioning
confidence: 99%